The design and cadaveric assessment of a new artifial first metatarsophalangeal joint replacement for the great toe - Nevin, Craig (Division of Biomedical Engineering, 2018)
The great toe is the part of the foot that most often requires surgical intervention. The first metatarsophalangeal joint (FMTPJ) is the most prominent joint of the great toe. Primary causes of FMTPJ failure are rheumatoid arthritis, osteoarthrosis and joint degeneration secondary to deformities such as hallux valgus, hallux rigidus or the trauma of previous surgery. FMTPJ prostheses are used to restore a measure of motion, correct deformities and relieve pain. FMTPJ replacement is most often indicated for elderly and less active patients but is contra-indicated for young, rheumatoid and active patients. The most common types of FMTPJ prostheses are made from silicone elastomer. Although these have been in use since the 1960's, there are many problems associated with these and all other types of FMTPJ prostheses. For example, recent research has shown that silicone elastomer metatarsophalangeal arthroplasties may cause severe, chronic silicone granulomatous disease. Also, previous studies of the pressure distribution under normal feet, and pathological feet before and after surgery, can be used to show that FMTPJ prostheses fail to restore normal weight-bearing. In this regard, FMTPJ arthroplasties perform little better than amputation. The reasons for the poor biomechanical performance of FMTPJ arthroplasty are not well documented. Existing theoretical models of FMTPJ function cannot be used to explain why almost all surgery of the first ray causes weight bearing to transfer to the lateral side of the foot. A new hypothesis of FMTPJ function was therefore formulated. It is known that the motions of the FMTPJ are linked to motions of the other bones of the foot and ankle because the strong fibrous tissues of the plantar aponeurosis connect the hallux to the calcaneus. However, it is hypothesised that the particular orientation of the bones at the final stages of the stance phase is crucial to the weight-bearing functions of the FMTPJ. A specification for a new prosthesis was therefore developed in accordance with the biomechanical principles contained in the hypothesis. Various potential designs of prosthesis were investigated, but a ball-and-socket configuration was selected because it appeared to allow the motions necessary to restore normal loading in the foot. Three slightly different prototype ball-and-socket FMTPJ prostheses were designed and manufactured. These prototypes were inserted into cadavers; which allowed the range of motion of the prototype prostheses to be assessed in relation to the constraints imposed by the strong fibrous attachments in the foot. Some of the rudimentary surgical techniques and the instruments required to insert and align the prostheses were developed. The various design features that had been incorporated in the different prototypes were assessed in terms of their relevance to ultimate performance of the arthroplasty. In order to verify the biomechanical design principles, cadaveric FMTP joints were tested for range of motion before and after inserting the prostheses. The results were compared to the range of motions obtained from a dry bone specimen, and to the most successful FMTPJ design to date- a double-stem silicone elastomer prosthesis. Finally, the results from all the tests were compared and discussed in relation to the original hypothesis about the function of the great toe. The results obtained from the new prosthesis were sufficiently encouraging to be able to recommend that the prototype be manufactured for further clinical trials. The new prosthesis was found to simulate the conditions that are necessary to re-establish normal weight-bearing patterns in the foot; such as an elevated centre of rotation for the proximal end of the first metatarsal bone, tension in the plantar aponeurosis, mobile bones in the arch, and weight-bearing by the first metatarsal. Previous prostheses used in FMTPJ arthroplasty are believed to be inadequate in that they do not restore at least one of these conditions, which ultimately lead to implant failure. Within the limits of cadaver trials, the new design has demonstrated that it has the potential to succeed.